Profile of Hypertension Patients Receiving Outpatient Care - Welly Salutondok; Syalomo Excellens Sangga Malole Ballo; Vidi Posdo A. Simarmata (CV. Inara, 2026)
Hypertension is a non-communicable disease with high prevalence and a major risk factor for cardiovascular disease, stroke, and kidney disorders. This condition is often asymptomatic, leading many patients to be diagnosed only after complications arise. Therefore, information on the profile of hypertensive patients is essential for healthcare planning and complication prevention. This study aimed to identify the profile of hypertensive patients at RSUD Naibonat during 2023-2024. A retrospective descriptive design was employed. Data were obtained from medical records of outpatient hypertensive patients at RSUD Naibonat during the study period. Total sampling was applied, including 152 patients meeting inclusion criteria. Variables analyzed included age, sex, body mass index, and blood pressure grade according to the Indonesian Society of Hypertension. Data were analyzed descriptively and presented as frequency distributions and percentages. Most hypertensive patients were elderly, particularly aged 67-76 years. Female patients outnumbered males. The majority had above-normal body mass index, predominantly type 2 obesity. Regarding blood pressure grade, grade 1 hypertension was most common, followed by isolated systolic hypertension and grade 2 hypertension. The profile of hypertensive patients at RSUD Naibonat during 2023-2024 was dominated by elderly individuals, females, and those with above-normal body mass index. These findings highlight the importance of early detection, risk factor management, and adoption of a healthy lifestyle to prevent hypertension progression and its complications.